Brain-based Learning in Textbooks: An Effort to Harmonize Emotion and Cognition in Learning History - Santosa, Ayi Budi; Fauzi, Wildan Insan; Tarunasena, (International Journal of Psychosocial Rehabilitation, 2020)
Brain-Based learning builds a learning design where emotions, cognition, reflection, social, and physical performed in harmony. Here lies the significance of combining brain-based learning and history textbooks. Researchers made brain-based learning as the theoretical basis of creating history textbook models. This research analyzed the influence of the history textbook model on the emergence of the brain-based learning aspect itself. The main limitation of this issue of research is how much the influence of a brain-based learning textbook based on the cognitive, social, reflective, emotional, and physical aspects of learners? The study used a pre-experimental approach with the design of one group pretest-posttest design. Neuroscience application to history textbook was effective to raise emotional, cognitive, and reflective elements but ineffective with social and physical learning system elements. Textbook effectiveness was highly determined by how teachers use it in the learning process. Teacher's role was enormous to give emotions to historical data in textbooks. The textbook was effective in providing history information, but it was the teacher's explanation that makes learners understand. The model textbook assisted students in relating various information, processing history information, assist them in thinking and interpreting history's events so that student's reflective thinking emerge. Reflection allowed students to get more insightful and meaningful information. The harmonization of cognitive and emotional elements on textbooks made students focus on learning and remembering historical facts. Students assessed the textbook as unchallenged and discourage for physical activity, cooperation and active participation and build history empathy.